Body mass index, weight change and risk of stroke and stroke subtypes: the Japan Public Health Center-based prospective (JPHC) study - Saito, I; Iso, H; Kokubo, Y; Inoue, M; Tsugane, S (International Journal of Obesity, 2011)
Objective: The Japan Public Health Center-based prospective Study examined the association of body mass index (BMI) and weight change with incident stroke in Japanese individuals, for whom BMI levels are generally low. Methods: We used initial data from 1990 to 1994 and 5-year follow-up surveys from 1995 to 1999. We calculated weight change over a 5-year period for 32 847 men and 38 875 women, aged 45–74 years, with no history of cardiovascular disease or cancer. Subjects were followed from the 1995–1999 survey to the end of 2005, and hazard ratios of self-reported BMI levels and weight change for incident stroke were estimated using Cox's proportional hazard models adjusted for potential confounders. Results: During the follow-up period (median 7.9 years) there were 2019 incident strokes, including subtypes. Multivariable-adjusted hazard ratios for all stroke events by BMI levels of 27.0–29.9 and 30 kg m–2 versus 23.0–24.9 kg m–2 were 1.09 (95% confidence interval 0.88, 1.36) and 1.25 (0.86, 1.84) in men (P for trend=0.22), and 1.29 (1.01, 1.65) and 2.16 (1.60, 2.93) in women (P for trend <0.001), respectively. A weight change of 10% in the previous 5 years was associated with total strokes and ischemic strokes in women. Conclusion: Higher BMI levels and a weight gain of 10% over 5 years were associated with an increased risk of stroke in women, whereas this association was weak in men.